Protected areas management - Zieger, Lee (Callisto Reference, 2015)
This book deals with the challenges faced by protected area managers and the techniques and methods to tackle them. Protected areas are the base of most national and international conservation strategies. Each of the protected areas needs a case-specific set of guidelines because of the numerous unpredictable elements in ecology matters, but a general issue in all these cases remains that of coping with human interaction. The management of these areas is full of challenges and the only way to gain understanding and achieve higher management possibilities is to exchange experiences and knowledge. Environmental managers are familiar with this fact and, along with scientists, are looking for more enhanced and novel solutions, both in relation with natural resources as well as human interactions in many issues about nature protection. The book elucidates reviews and research results on protected area management, as well as several case studies derived from across the world with the goal of enhancing management effectiveness of these areas.